Monumenten dendrochronologisch gedateerd (3) - Dirk Jan de Vries (Bulletin KNOB, 1990)
Datings on the ground of art- or building-historical characteristics do not always prove to be as reliable for monuments from late medieval times. Thanks to the presence of old wooden constructions and the possibility to saw or to drill samples from these constructions the building-history of some Dutch buildings could be completed or readjusted. Wooden samples of objects along the eastern border proved to be dateable with the aid of West-German Standard curves. In the more westerly situated commercial towns a dendrochronological dating sometimes was harder, the wood in these parts having its origin in different regions.